2019
DOI: 10.2174/1570159x16666180911121847
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury Altered Normal Brain Signaling Pathways: Implications for Novel Therapeutics Approaches

Abstract: Traumatic brain injury (TBI) is the main reason of lifelong disability and casualty worldwide. In the United state alone, 1.7 million traumatic events occur yearly, out of which 50,000 results in deaths. Injury to the brain could alter various biological signaling pathways such as excitotoxicity, ionic imbalance, oxidative stress, inflammation, and apoptosis which can result in various neurological disorders such as Psychosis, Depression, Alzheimer disease, Parkinson disease, etc. In literature, various report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 97 publications
1
14
0
1
Order By: Relevance
“…3,4 Primary injury due to initial impact is the main factor determining TBI prognosis, whereas secondary injury, which is triggered by primary injury, the results from neurochemical processes and intracellular signaling pathways, such as oxidative stress, inflammatory response, neuronal apoptosis and other detrimental factors, which aggravate brain primary injury after TBI. 5 Therefore, alleviating secondary injury by intervening in neurochemical processes and intracellular signaling pathways is very important in the treatment of TBI.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Primary injury due to initial impact is the main factor determining TBI prognosis, whereas secondary injury, which is triggered by primary injury, the results from neurochemical processes and intracellular signaling pathways, such as oxidative stress, inflammatory response, neuronal apoptosis and other detrimental factors, which aggravate brain primary injury after TBI. 5 Therefore, alleviating secondary injury by intervening in neurochemical processes and intracellular signaling pathways is very important in the treatment of TBI.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the mammalian target of rapamycin (mTOR) pathway plays an important role in a variety of physiological functions of the nervous system, such as nerve cell growth, survival, development of dendritic cells during differentiation, and synaptic plasticity (Don et al, 2012 ). Some studies have shown that mTOR inhibition prevents neuronal injury and death after TBI, while others have shown that increased mTOR signaling after injury promotes cell regeneration and functional recovery (Rana et al, 2019 ). The occurrence of mitochondrial autophagy has been reported after TBI and is a powerful target (Chu et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…TBI causes multiple functional de cits in the brain, such as sensory, motor, and cognitive functions, which related to the damaged regions [2]. Neurons and glial cells in damaged tissue release excessive glutamate leading to excitatory toxicity; energy metabolism disorder results in ATP depletion, mitochondrial dysfunction, oxidative stress, and other events leading to neuron death [3][4][5][6]. Besides, in ammatory mediators produced by damaged cells recruit cerebral microglia and peripheral immune cells which release in ammatory factors, thus promoting secondary neuronal damage [7].…”
Section: Introductionmentioning
confidence: 99%